Knowledge of HIV/AIDS among adolescence at intellectual academy in Kumarigal-7, Tushal, Kathmandu, Nepal - Rana, G (Journal of Chitwan Medical College, 2015)
Introduction: Young people in Nepal are vulnerable to HIV/AIDS because of their poor knowledge of sexual health, unsafe sex practices, and limited use of condom. Adolescence should be targeted for prevention programs because it is possible to modify adolescents’ behavior as they may not have developed unsafe practices or if developed, these behaviors are not deeply rooted. The objective of this study was to identify knowledge of HIV/AIDS among adolescence. Methods: A descriptive design was used. A total of 50 adolescence were selected by using simple random sampling technique (lottery method) from Intellectual Academy, Kumarigal-7, Tushal, Kathmandu. Self administered structured questionnaire was used to collect the data from January 10, 2006 (2062-9-29) to April 8, 2006 (2062-12-26). Results: Only 66% of adolescence had knowledge that HIV/AIDS is communicable disease. Regarding transmission of HIV/AIDS, 90% adolescence answered transmit through unprotected sexual contact, 84% through contaminated blood products, 90% through infected mother to child transmission, 52% through use of shared razors and 94% through use of contaminated needles and syringes. Regarding preventive measures, All the participants had knowledge of using condom, screening of blood before transfusion, and avoid sharing of needles and syringes as preventive measures while 92% as one faithful sex partner and 52% as avoid use of shared razors. Conclusion: Most of adolescence had knowledge regarding mode of transmission of HIV/AIDS through unprotected sexual contact; infected mother to child transmission and use of contaminated needles and syringes. Likewise, on the context of signs of AIDS and preventive measures on HIV transmission, adolescence had knowledge. DOI: http://dx.doi.org/10.3126/jcmc.v4i4.11971